Pengembangan Aplikasi Web dan Mobile Pada Monitoring dan Evaluasi Program Tahfidz Quran - Ridwan Ridwan; Cut Mutia (PTE FTK UIN Ar-Raniry, 2022)
Madrasah Ulumul Qur'an (MUQ) Pidie Regency is one of the educational institutions that has a tahfidz program. Recently, the recording of the memorization of the Qur'an for each student is carried out on one sheet of paper. The existence of information technology requires an educational institution to implement IT applications properly. This study aims to build a fine monitoring and evaluation system for tahfidz qur'an in terms of presenting data to the MUQ of Pidie Regency and parents. Data information on the proposed web and mobile application system is in the form of information data in kinds of tables, text, graphs and reports of rote achievement. The research method used research and development approach with an application development model (the waterfall). The applications used the concept of web services that connected between web and mobile applications. The results showed that the development of monitoring and evaluation system in the form of web and mobile applications for data management on the development of tahfidz by presenting data in the form of text, graphs and tables. This effectively provides monitoring and evaluation functions which easier, faster and more efficient. The results of the application effectiveness test showed that the average value of the percentage of 19 questions was 96%. Based on the results of the questionnaire, the average value is above 70%. Generally, this application is very helpful for parents in monitoring the development of their child's memorization.